The effectiveness of the referral system in primary health care in the West Rand region : a normative-ethical study with special emphasis on traditional healers - Molepo, Edward R. (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Phil.)--Stellenbosch University, 2000.